Developing a net-centric foresight model for the management of emerging risks - Mathew, Ferns Mathew (2019)
With global risks increasing in magnitude, speed and cross-sectoral complexity, there is a critical need to foresee disruptive developments in an accurate, expeditious and cost-effective manner. Scholars concur that emerging risks may overwhelm the global capacity to contain them due to large-scale systems interdependencies and increasing risk propagation pathways. Therefore, this qualitative study developed a whole-system based Strategic Foresight Model (SFM) that can rapidly identify and manage emerging transboundary risks. There were two consecutive methodological phases in this thesis: the first involved an instrumentalist approach to develop the SFM while the latter entailed a cross-comparative study to validate the new model. The instrumentalist approach plugged critical gaps in the traditional foresight process by incorporating elements such as a net-centric foresight platform; open source environmental scanning; and a specifically-designed Cone of Risk for the diagnosis stage of the foresight process. Instrumentalism aided the SFM’s development by situating the new model within the ephemeralization-complex adaptive system theoretical paradigm; identifying key components of the Cone of Risk diagnosis tool; and subjecting the SFM to random case studies and an individual instrument test. Since The SFM had also posited itself as a net-centric alternative to closed-door, protracted and resource-intensive traditional Delphi studies, the World Economic Forum (WEF)’s annual global risk reports, particularly for the years 2016 and 2017, were used as comparative benchmarks. A group survey comprising 34 key respondents drawn from a think tank, risk-savvy professionals and post-graduate students managed to pre-emptively identify 49 global risks via the SFM – including all 30 risks subsequently published by the WEF for the year 2017. Research validation was achieved through qualitative comparative analysis which, in turn, was facilitated by standardizing risk descriptions and taxonomy used by the WEF. The SFM will significantly impact the application of rapid risk foresight, open governance, and national policy planning, amongst others, as it can seamlessly integrate the emergent quadruple helix model into a single net-centric matrix – one that will be economical, robust and highly-adaptable for users.